(untitled) (Itinera, 2016)
In the second chapter of The Time-Image, Deleuze addresses the conditions of possibility of a semiology of cinema. These conditions depend on the relations between cinema and language: under what conditions can cinematic images and signs be understood as a language? In other words, (how) can cinematic images and signs be inscribed in the discursive plane of the signifiable? Discussing Christian Metz’s semiological approach of cinema, Deleuze argues that the structural conditions of linguistics and of post-Saussurian semiology cannot adequately render intelligible the specificity of cinematic semiosis. Drawing on Louis Hjelmslev’s semiotics, Deleuze redefines the specificity of a relation of designation distinct from a relation of signification (strictly linguistic), a specificity that concerns the fact that the designative relation is antecedent and heterogeneous to any signifying relation. Put differently, the very constitution of the sign is redefined: in opposition to semiology, semiotics becomes the study of images and signs as (1) being independent of language in general and (2) expressing a “non-language material”. This article explicates the importance of Hjelmslev’s semiotic theory in The Time-Image by offering a detailed account of the constitution of the sign in Hjelmslev’s Prolegomena to a Theory of Language and by tracing Deleuze’s earlier appreciation of Hjelmslev in Anti-Oedipus and its intricate relation to his appreciation of Jean-François Lyotard’s theory of designation in Discourse Figure.